Proyecto de factibilidad para la creación de una empresa productora y comercializadora de camisas con logos-bordados culturales de la provincia de Loja - Bustamante Bustamante, Wilmer Antonio (2016)
The overall objective of this research was to determine the feasibility of implementing a producer and marketer of shirts with logos business - cultural embroidery in the province of Loja. The methods used were: quantitative research method, library research method, statistical method, method of field research, projective method research and qualitative research method. Regarding the survey techniques male users of the province were used; interviews were used in addition to current manufacturers of shirts; likewise the observation of current production processes used for making this type of product. As data can be mentioned: In the study of the potential of the product market demand for 86386 base year it was determined as 54423 real demand, as effective demand and expected demand as 87077. The annual supply is 12168 and then the unsatisfied demand is obtained 74909 shirts with embroidered logos annually. The technical study installed capacity of 7200 shirts with embroidered logos cultural obtained and a capacity utilization of 5040. In addition, the company will be located in the southern sector of the city of Loja, in the streets: November 18 and Catacocha, according to the results of the analysis of the weighted matrix. The distribution of the plant, which will have a good atmosphere in keeping with the nature of work was then determined. In organizational analysis, the total of 7 employees who are required for administration and manufacturing area was established. Likewise, the organizational structure was formed, the constitution of the company as a corporation, where also the minutes of such constitution is included and this section concludes with a manual functions for all persons working in the business. In the financial study it was obtained that the total fixed assets is USD. 10023.20; USD deferred assets. 2271.15; current assets and USD. 7510,11, with a total of USD. 19804,46; as the initial budget is financed; 50.49% for the contributing partners and the rest is the 49.51% who were 10,000.00 will be financed with a loan from the National Development Bank. In the income statement, net profit margin of USD was obtained. 35,671,22 for the first year of operations. The financial evaluation positive net present value of USD was obtained. 184485,41; the internal rate of return is 164.01%; benefit ratio of 1.24; capital recovery period will be 7 months and 11 days, and ended with the sensitivity analysis which shows that the company can withstand cost increases 15.40%, and the drop in income 12.36, for positive net flows.